Genomic signatures of extensive inbreeding in Isle Royale wolves, a population on the threshold of extinction - Robinson, Jacqueline A.; Raikkonen, Jannikke; Vucetich, Leah; Vucetich, John A.; Peterson, Rolf O.; Lohmueller, Kirk; Wayne, Robert (Digital Commons @ Michigan Tech, 2019)
The observation that small isolated populations often suffer reduced fitness from inbreeding depression has guided conservation theory and practice for decades. However, investigating the genome-wide dynamics associated with inbreeding depression in natural populations is only now feasible with relatively inexpensive sequencing technology and annotated reference genomes. To characterize the genome-wide effects of intense inbreeding and isolation, we performed whole-genome sequencing and morphological analysis of an iconic inbred population, the gray wolves (Canis lupus) of Isle Royale. Through population genetic simulations and comparison with wolf genomes from a variety of demographic histories, we find evidence that severe inbreeding depression in this population is due to increased homozygosity of strongly deleterious recessive mutations. Our results have particular relevance in light of the recent translocation of wolves from the mainland to Isle Royale, as well as broader implications for management of genetic variation in the fragmented landscape of the modern world.